Subcycle observation of lightwave-driven Dirac currents in a topological surface band. (18th October 2018) - Reimann, J.; Schlauderer, S.; Schmid, C.; Langer, F.; Baierl, S.; Kokh, K.; Tereshchenko, O.; Kimura, A.; Lange, C.; Güdde, J.; Höfer, U.; Huber, R.
Abstract Harnessing the carrier wave of light as an alternating-current bias may enable electronics at optical clock rates1 . Lightwave-driven currents have been assumed to be essential for high-harmonic generation in solids2–6, charge transport in nanostructures7, 8, attosecond-streaking experiments9–16 and atomic-resolution ultrafast microscopy17, 18 . However, in conventional semiconductors and dielectrics, the finite effective mass and ultrafast scattering of electrons limit their ballistic excursion and velocity. The Dirac-like, quasi-relativistic band structure of topological insulators19–29 may allow these constraints to be lifted and may thus open a new era of lightwave electronics. To understand the associated, complex motion of electrons, comprehensive experimental access to carrier-wave-driven currents is crucial. Here we report angle-resolved photoemission spectroscopy with subcycle time resolution that enables us to observe directly how the carrier wave of a terahertz light pulse accelerates Dirac fermions in the band structure of the topological surface state of Bi2 Te3 . While terahertz streaking of photoemitted electrons traces the electromagnetic field at the surface, the acceleration of Dirac states leads to a strong redistribution of electrons in momentum space. The inertia-free surface currents are protected by spin–momentum locking and reach peak densities as large as two amps per centimetre, with ballistic mean free paths of several hundreds of nanometres, opening up a realistic parameter space for all-coherent lightwave-driven electronic devices. Furthermore, our subcycle-resolution analysis of the band structure may greatly improve our understanding of electron dynamics and strong-field interaction in solids. Time- and angle-resolved photoemission spectroscopy reveals how Dirac fermions in the band structure of the topological surface state of Bi2 Te3 are accelerated by the carrier wave of a terahertz-frequency light pulse.